Morphological Characteristics of Prostate in Mammals (International Journal of Medical and Surgical Sciences, 2014)
The prostate gland is present in all male mammals and its ejaculate secretion plays a direct role in female reproductive success. Despite the importance of their function, morphology and chemical nature of their secretion in non-human mammals is not described in detail in scientific literature. To better define the morphological description of this gland, quantitative methods such as stereology have allowed identification for instance, of the number and percentage of glandular cells. These analyses however, have only been described in some animals. Therefore, the aim of this review was to discuss what is known about the anatomical, histological, histochemical and stereological characteristics of mammalian prostate to provide information that could be useful in the field of production and yields of breeding animals for consumption, and to improve reproductive management in laboratory animals used as models in research.
Keywords: Prostate; Mammals; Morphology